Vancomycin minimum inhibitory concentration, host comorbidities and mortality in Staphylococcus aureus bacteraemia. (26th February 2013) - Holmes, N. E.; Turnidge, J. D.; Munckhof, W. J.; Robinson, J. O.; Korman, T. M.; O'Sullivan, M. V. N.; Anderson, T. L.; Roberts, S. A.; Warren, S. J. C.; Gao, W.; Johnson, P. D. R.; Howden, B. P.; et al.
Abstract We reported an association between elevated vancomycin MIC and 30‐day mortality in patients with Staphylococcus aureus bacteraemia (SAB), including patients with methicillin‐susceptible S. aureus (MSSA) treated with flucloxacillin. A detailed analysis of comorbidities and disease severity scores in the same cohort of patients was performed to ascertain if unknown clinical parameters may have influenced these results. The association between elevated vancomycin MIC and 30‐day mortality in SAB remained significant (p 0.001) on multivariable logistic regression analysis even when accounting for clinical factors. In addition, the association persisted when restricting analysis to patients with MSSA bacteraemia treated with flucloxacillin. This suggests that elevated vancomycin MIC is associated with but not causally linked to an organism factor that is responsible for increased mortality.